2021
DOI: 10.1186/s12961-021-00686-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of – and first response to – injuries in Nepal: a review of policies and legislation

Abstract: Background Injuries, the cause of an estimated 4.5 million deaths annually and many more disabilities worldwide each year, are the predictable outcome of particular circumstances. One of the most effective ways to prevent injuries is through policy and legislation. The aim of this research study was to identify and critically review all policy and legislation in Nepal that had the potential to prevent injuries. Methods We identified legislation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 26 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…In Nepal, a policy review identified that institutional arrangements and resource allocation for road safety were inadequate. 13 The lack of coordination of road safety sectors is a challenge globally 24 25 as well as in Nepal. Many of the participants in this study had the opportunity to meet and discuss road safety with those working in other sectors, for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Nepal, a policy review identified that institutional arrangements and resource allocation for road safety were inadequate. 13 The lack of coordination of road safety sectors is a challenge globally 24 25 as well as in Nepal. Many of the participants in this study had the opportunity to meet and discuss road safety with those working in other sectors, for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the institutional structures necessary to implement these laws are still in development. 13 The research questions prioritised in this study emphasise the need for evidence to support both national development plans 8 and safer roads and transport in Nepal. 38 Existing road safety policies are mostly only partially implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local authorities failing to invest in road infrastructure and safety was another concern of our participants. This is there despite there being 21 legal documents and 14 policy documents relating to road traffic injuries or their prevention in Nepal as identified by a recent policy and legislation review study ( Pant et al, 2021 ). The National Transport Policy 2001, Nepal Road Safety Action Plan 2013–2020, and the current 20-year Master Plan for Strategic Road Networks (2002–2022) all include road crash reduction recommendations, but just like most of the policy documents, they include little consideration of the allocation of resources, leadership or robust monitoring and evaluation resulting in all these strategic approaches remaining on paper without implementation ( Pant et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is there despite there being 21 legal documents and 14 policy documents relating to road traffic injuries or their prevention in Nepal as identified by a recent policy and legislation review study ( Pant et al, 2021 ). The National Transport Policy 2001, Nepal Road Safety Action Plan 2013–2020, and the current 20-year Master Plan for Strategic Road Networks (2002–2022) all include road crash reduction recommendations, but just like most of the policy documents, they include little consideration of the allocation of resources, leadership or robust monitoring and evaluation resulting in all these strategic approaches remaining on paper without implementation ( Pant et al, 2021 ). In low- and middle-income countries, it can be anticipated that with limited resources and lack of political will, issues such as road expansion and building safety infrastructure are not addressed quickly ( Kayani et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%